Zika virus epidemiology: From Uganda to world pandemic, an update (2018)
Zika virus (ZIKV) infection is an emergent worldwide public health problem. Historically, 84 countries have reported vector-borne ZIKV transmission, 61 of which report on-going transmission. It is a Flavivirus transmitted through arthropods belonging to the Aedes genus. Since 2015, ZIKV infections have increased dramatically; with 1.3 million people infected during 2015 in Brazil alone. This paper's objective is to highlight the conjectural epidemiological points of the virus' dissemination. The digital archives Pubmed, MEDLINE, EMBASE and Cochrane were searched for papers that assessed aspects of ZIKV transmission and epidemiology. The first isolation occurred in Uganda in 1947. Since then, important outbreaks were documented globally. Consequently, an emergent public health problem arose from a rapidly increasing incidence and its association with the development of neurological diseases such as microcephaly and Guillain-Barré syndrome. Key factors in the successful containment of outbreaks include surveillance of mosquitos in the neighbourhood, an early mosquito control treatment, an assertive information campaign, and the involvement of the local population and healthcare workers. As such, while ZIKV seems to be spreading globally in a similar manner to other arboviruses, such as Dengue and Chikungunya viruses, it can also be rapidly contained due to the pre-existing availability of necessary resources and regulatory tools as control measures. This review aims to provide a description of those characteristics of ZIKV infection that may be useful in the construction of effective outbreak control strategies. Copyright © Cambridge University Press 2018.